Case Image: Cutaneous Leiomyoma - Sunil Jaiswal; Shraddha Uprety; Pratichya Thapa; Prakriti Lamichhane (Clinical Case Reports)
ABSTRACT Cutaneous leiomyomas are rare benign smooth muscle tumors that often present as painful dermal nodules; however, they can be asymptomatic too. Histopathology remains the gold standard for diagnosis and warrants screening for Hereditary Leiomyomatosis and Renal Cell Carcinoma (HLRCC) in patients presenting with multiple lesions.